Migração de rádio: do AM ao FM, tradição, inovação e reconfiguração na Rádio Educadora do Maranhão - FEITOSA, Gutemberg de Sousa (2021)
This research presents as a problematization the repositioning of Educadora Radio from Maranhão, AM 560, a Catholic broadcaster, in the context of the migration from the AM band (Modulated Amplitude) to FM (Modulated Frequency). It is about identifying the challenges and opportunities that the migration process could bring to the broadcaster. We seek to revisit the characteristics and themes of radio co=unication, understand the AM/FM migration and its related themes, study about marketing repositioning, business models. Only then do we present a proposal for new progra=ing for the station after migrating to FM, which, in tum, will enable the Catholic station of the Archdiocese of São Luís to re-qualify itself with the listening public and the advertising market, without failing to identify, and try to mitigate the dile=as arising from migration. It is then a comparative co=unication work (methodology) of Educadora Radio from Maranhão with other Catholic radio stations listed here. It is our intention to help consolidate a strong brand that allows the AM broadcaster not only to survive, but to develop and reach its best possible version within the spectrum of the Modulated Frequency.